Edukasi Menggunakan Booklet Preconception Care Meningkatkan Pengetahuan dan Self Efficacy Calon Pengantin - Yunita Wulandari; Wahyu Dwi Aguissafutri; Wahyuningsih Safitri (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: The bride and groom are part of the preconception care program targets. The period before conception for the bride and groom is very important to consider in order to prepare for a healthy pregnancy. Aim of this study is to analize the effect of giving the preconception care booklet on the knowledge and self efficacy of the prospective bride and groom (catin). Methods: The research method used was quantitative with a quasi experimental approach pre and post test without control. with a total sample of 56 people (28 catin), assessing knowledge and self-efficacy using a questionnaire. The intervention given to respondents was education with preconception booklets. Results: The results of the analysis showed that in the pre and post groups both knowledge and self-efficacy obtained a p-value of 0.000 <0.05 so that there was a difference between the pre-test and post-test levels of knowledge on reproductive health and sef efficacy of the prospective bride and groom. This means that Ha is rejected and Ho is accepted. Conclusion: Recommendation in this study is the influence of giving the Preconception Care Booklet on the knowledge and Self Efficacy of the bride and groom.